Phytosociological Study in Two Aquatic Environments Djedrra Dam and Battoum (Souk Ahras) - Dahbane Bouchra (My University, 2026)
The present study is dedicated to the phytosociological study of the vegetation in tow aquatic environments El Battoum and Djedrra Dam region (Wilaya of Souk-Ahras). The inventories of the two stations allowed for floristic list presented by 72 species, distributed across 26 families. There were 48 species from 9 families at the El Battoum station and 56 species from 22 families at the Djedrra dam station. The Asteraceae and Plantaginaceae with 28 and 11 species were the most widespread in these families. From a biological standpoint, we saw that Hemicryptophytes predominated (51%). Diversity analysis (H′ > 3) in the Battoum and Djedrra Dam indicates a high level of species richness. ------------------------------------------------------------------------------------------------------------------ تُركز هذه الدراسة على التحليل النباتي الاجتماعي لبيئتين مائيتين منطقة البطوم وسد جدرة (ولاية سوق أهراس). وقد أتاحت عمليات حصر الأنواع في المحطتين إعداد قائمة نباتية تضم 72 نوعًا، موزعة على 26 فصيلة. وُجد 48 نوعًا من 9 فصائل في محطة البطوم، و56 نوعًا من 22 فصيلة في محطة سد جدرة. وكانت الفصيلتان النجمية واللسانية لأكثر انتشارًا، حيث ضمت الأولى 28 نوعًا والثانية 11 نوعًا. ومن الناحية البيولوجية، لوحظ غلبة النبات شبه مطمور بنسبة 51%. يشير تحليل التنوع (H′ > 3) في البطوم وسد جدرة الى مستوى عال من ثراء الانواع ----------------------------------------------------------------------------------------------------------------- La présente étude est consacrée à l'étude phytosociologique en deux environnements aquatique région d'El Battoum et Barrage Djedrra (Wilaya de Souk-Ahras). Les inventaires des deux stations ont permis d'établir une liste floristique présentée par 72 espèces, réparties sur 26 familles. Il y avait 48 espèces provenant de 9 familles à la station d'El Battoum et 56 espèces provenant de 22 familles à la station du barrage de Djedrra. Les Asteraceae et les Plantaginaceae avec 28 et 11 espèces étaient les plus répandues dans ces familles. D'un point de vue biologique, nous avons constaté que les hémicryptophytes prédominaient (51%). L'analyse de la diversité (H′ > 3) dans le Battoum et le barrage de Djedrra indique un niveau élevé de richesse spécifique.
Keywords: phytosociology; aquatic environnements; inventories; Battoum; Djedrra Dam Souk Ahras.; علم النبات الاجتماعي، حصر الانواع، بيئتين مائيتين، البطوم، سد جدرة; سوق أهراس